Design and fabrication of a stainless steel base for biomechanical testing of Wistar rat abdominal wall. (2014)
The mechanical property of materials allows us to know how and how their performance will then be subject to the conditions for which it was designed. The biomechanical properties of biological tissues give an approximation to loads which it may be subjected in its biological environment. The objective of this project was to design a support to allow the biomechanical plunger tests on a sample of tissue from the abdominal wall of Wistar rat. The 1010 stainless steel support was 102 mm diameter and 50 mm of high, and 40 mm diameter extrusion in the middle was attached to the Instron 3366 universal testing machine